Pemarkah Sangkalan fa Dalam Bahasa Dawan (Sebuah Kajian Awal) - Isu, Rudolof Jibrael (Universitas Persatuan Guru 1945 NTT, 2018)
This initial research review premarket Disclaimer sentences in languages that include the study of the form of Dawan and distribution. Research data are restricted to the realm of the subject in the language of Dawan. This research is descriptive research because it exposes the data as is, as found by the time the research was conducted. Sample research location is the old Village, Kampung Manulai II, Alak, Kupang. Method of data collection is the interview and documentation study with data collection techniques are techniques of recording and see-note. The data were analyzed qualitatively-argumentative with inductive methods. The initial results of the study indicate that there is a linguistic phenomenon to premarket Disclaimer language syntax in Dawan has characteristics typical of appropriate specificity of context grammatically the military discharging phenomena grammatically. The peculiarities which show specificity criterion and characteristic of pertaining linguistic phenomenon used in sentence-level language usage can be seen in Dawan premarket Disclaimer, as reflected in the distribution of life forms and aspects grammatical basis by fa. Pemarkah this has a significance in grammatically because of grammatical typology and with regard to the use of languages in the community of speakers Dawan.